SOCIAL ENTREPRENEURSHIP CONDITION FOR THE DEVELOPMENT OF THE LOCAL ECONOMY - Borowska, Alina (Ekonomia i Prawo. Economics and Law, 2013)
Social entrepreneurship, an element of “new social economy", operating under the Third Sector, is able to capture in an innovative way and to satisfy these social needs, which are unlikely to be fulfilled by the charity institutions and the state, due to their bureaucratic attitude, resisting change, lack of flexibility, innovation and creativity. The development of local entrepreneurship should be strongly supported by the local governments, universities and the media, because it can bring many socio-economic benefits to the individual, society and the world.